The influences of Cr-tolerant rhizobacteria in phytoremediation and attenuation of Cr (VI) stress in agronomic sunflower (Helianthus annuus L.). (July 2017) - Bahadur, Ali; Ahmad, Rizwan; Afzal, Aftab; Feng, Huyuan; Suthar, Vishandas; Batool, Asfa; Khan, Aman; Mahmood-ul-Hassan, Muhammad
Abstract: Chromium contamination of agronomic soil has to turn into a serious global problem. This research was pointed to assess the effects of three Cr-tolerant rhizobacteria (SS1, SS3, and SS6) on sunflower growth and heavy metal uptake under Cr smog i.e. 20, 30 and 40 ppm using K2 Cr2 O7 . Root promotion assay and pot experiment were conducted to investigate and evaluate the effects of Cr tolerance rhizobacteria and Cr accumulation capacity of sunflower. From root promotion assay non-significant variation was observed in the root length between SS1 and SS3 compared with un-inoculated whereas SS6 enhanced the root length in the absence and presence of chromium. In addition, inoculation with rhizobacteria alleviated the Cr concentration and endorsed plant growth by enhancing Cr accumulation in sunflower. At different Cr levels, the Cr concentration in shoot was improved by each rhizobacterium though their difference was non-significant with each other, while the percentage increase was half as the Cr level doubled. Different rhizobacterium inoculation significantly ( P < 0.05) affected the physiological and morphological characteristics of sunflower and increased the plant height, stem diameter, head diameter, grain yield, oil content of seeds, and total biomass, and among them, SS6 observed best followed by SS1 and SS3 comparing with un-inoculated. Our study illustrates an assessment about Cr-tolerant bacteria and their influences and recommends that these bacteria can effectively be used for crop improvement which provides a potential approach for Cr phytoremediation. Graphical abstract: Highlights: Chromium tolerant rhizobacterial behaviors were explored with different Cr stress levels in sunflower. Chromium tolerant rhizobacteria could promote the growth characteristics and Cr accumulation of sunflower. Matching of Cr-tolerant rhizobacteria and sunflower is significant in phytoremediation of Cr-contaminated soil.